EFFECTIVENESS OF GROUP GUIDANCE SERVICES USING SELF-CONTROL TECHNIQUES IN OVERCOMING ACADEMIC PROCRASTINATION ATTITUDES - Harahap, Elfa Khairani; Wahyuni, Sri (FORUM PAEDAGOGIK, 2024)
This research aims to determine the effectiveness of group guidance services using self-control techniques in overcoming students' academic procrastination attitudes. This research uses a one group pre test post design research design using purposive sampling technique. The population in this research numbered 70 and the sample numbered 14 from class VII-C of SMP IT Al-Hijrah 2 Deli Serdang. The data collection tool in this research uses an academic procrastination scale data collection tool that has been approved by experts. The research results showed that academic procrastination attitudes decreased after the posttest compared to the pretest scores, therefore group guidance services were effective in overcoming academic procrastination attitudes of class VII-C students at SMP IT Al-Hijrah 2 Deli Serdang. The implementation of group guidance services using self-control techniques is effective in overcoming students' academic procrastination because students create and implement a daily schedule that allows students to know what activities they will carry out in a full day and students are not inclined to just use one activity using this daily schedule. become a program to reduce students' academic procrastination attitudes. This program can also be used as an effort to reduce students' academic procrastination attitudes for schools and future researchers.